Cultural perceptions and natural protections: a socio-legal analysis of public participation, birdlife and Ramsar Wetlands in Japan. Issue 1 (May 2018) - Hamman, Evan
Abstract : The aim of this article is better to understand the relationship Japanese people have with birdlife, wetlands and environmental law. The article uses a case study of the Japanese 'red-crowned' crane (the tancho ) and Ramsar sites in Eastern Hokkaido to examine Japan's environmental governance systems and actors and the extent to which they utilize the principle of public participation. The topic is significant because of the urgency with which wetlands and birdlife are being lost in East Asia and the impacts such loss will have on communities and national identity. The observations in this article have relevance for neighbouring Asian countries like China and Korea, both of which have their own cultural perceptions and legal protections to consider.